Socio-Economic Impacts of Dairy Cooperative - Chaudhary, Balak; Upadhyaya, Mukul (Economic Journal of Development Issues, 2015)
A study was conducted in Adarsha Milk Producer Dairy Cooperative, Mahuli, of Saptari district to find out socio-economic impact of dairy cooperative during May 2008 to Dec.2008. Response from 224 milk producing farmers were randomly collected, stored and analysed using Microsoft excel program. Different sources of income have been recorded and analysed with major category as main crop, cash crop, dairy goat farming and service in organizations. Among them, dairy was found to be the highest income contributor (55%) to the rural farmers. Moreover, dairy was found to be the symbol of pride, prestige and religious priority for the studied community.DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11859Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 15-23